Eye movement desensitisation and reprocessing therapy v. stabilisation as usual for refugees: randomised controlled trial. (October 2016) - ter Heide, F. Jackie June; Mooren, Trudy M.; van de Schoot, Rens; de Jongh, Ad; Kleber, Rolf J.
Abstract : Background: Eye movement desensitisation and reprocessing (EMDR) therapy is a first-line treatment for adults with post-traumatic stress disorder (PTSD). Some clinicians argue that with refugees, directly targeting traumatic memories through EMDR may be harmful or ineffective. Aims: To determine the safety and efficacy of EMDR in adult refugees with PTSD (trial registration: ISRCTN20310201). Method: In total, 72 refugees referred for specialised treatment were randomly assigned to 12 h of EMDR (3×60 min planning/preparation followed by 6×90 min desensitisation/reprocessing) or 12 h (12×60 min) of stabilisation. The Clinician-Administered PTSD Scale (CAPS) and Harvard Trauma Questionnaire (HTQ) were primary outcome measures. Results: Intention-to-treat analyses found no differences in safety (one severe adverse event in the stabilisation condition only) or efficacy (effect sizes: CAPS –0.04 and HTQ 0.20) between the two conditions. Conclusions: Directly targeting traumatic memories through 12 h of EMDR in refugee patients needing specialised treatment is safe, but is only of limited efficacy.